The Transformation of the Hungarian Defence Forces - Bárány, Zoltán Gábor; Kiss, Álmos Péter; Szalkai, Patrik György (Honvédségi Szemle – Hungarian Defence Review, 2025)
With the end of the Cold War, Hungary, like most European nations, allowed its considerable military capability to decline. As international crises followed each other in the early 21st century, the country’s leadership realised that Europe’s security situation was deteriorating and a credible deterrent force was needed to protect national borders and sovereignty. The Hungarian Defence Forces embarked on an ambitious transformation program in 2017, the two pillars of which are the modernisation of the entire defence sector and the creation of armed forces superior to all possible opponents. The paper provides a brief overview of the HDF transformation process that has taken place so far.